1974
DOI: 10.1159/000122323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraventricular Infusions of Norepinephrine and Dopamine on LH Release and Ovulation in the Rabbit

Abstract: The infusion of 50 µg norepinephrine (NE) into the third ventricle of the brain was found to be highly effective in stimulating the release of an ovulatory surge of LH from the pituitary gland in estrogen-primed rabbits. Intraventricular dopamine (D), in dosages of 5 and 50 µg, was not only completely ineffective in inducing ovulation, but the higher dosage actually blocked the ovulatory effect of NE, often for a month or more after infusion. In experimentts in which LH was measured by radioimmunoassay, intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Consequently, the results lend further credence to the postulated role of NE in stimulating the preovulatory release of LH and that induced by ovarian steroids [Sawyer et al, 1947;McCann and Moss, 1975]. The present results and those of previous studies [Rubinstein and Sawyer, 1970;Sawyer et al, 1974] also raise the possibility that E might play a physiological role as a stimulator of LH release. Recently, terminals of epinephrinergic neurons have been shown to be present in the hypothalamus [H ó k felt et al, 1974] and they may play a physiological role.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, the results lend further credence to the postulated role of NE in stimulating the preovulatory release of LH and that induced by ovarian steroids [Sawyer et al, 1947;McCann and Moss, 1975]. The present results and those of previous studies [Rubinstein and Sawyer, 1970;Sawyer et al, 1974] also raise the possibility that E might play a physiological role as a stimulator of LH release. Recently, terminals of epinephrinergic neurons have been shown to be present in the hypothalamus [H ó k felt et al, 1974] and they may play a physiological role.…”
Section: Discussionsupporting
confidence: 88%
“…However, the effects of intraventricular monoamine injections should be interpreted with caution as there is evidence that such effects are non-specific (Hokfeldt & Fuxe, 1972). In oestrogen-primed rabbits the intraventricular injection of noradrenaline stimulated LH release, but dopamine not only failed to release LH but even blocked the ability of noradrenaline to induce such a rise (Sawyer et al, 1974). Similarly more recently, using ovariectomized steroid-primed rats, it has been found that the intraventricular administration of dopamine had no stimulatory effect on LH release in contrast to noradrenaline (Kreig & Sawyer, 1976).…”
Section: The Gonadotrophins (Lh and Fsh)mentioning
confidence: 95%
“…Hypothalamic norepinephrine (NE) plays an important role in the control of reproduction because its effects on sexual behavior and on the secretion of gonadotropin, especially luteinizing hormone (LH), are firmly established (Sawyer et al 1974, Kalra & Kalra 1983, Etgen et al 1992. In contrast, biochemical and molecular events in noradrenergic neurons in the brainstem where hypothalamic NE is derived have received little attention.…”
Section: Introductionmentioning
confidence: 99%